Analyzing the Types and Implementation of Elicitation Strategies in English Classroom at Al Islam Boarding School - Ikhlas Abdi Perkasa (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to examine the elicitation strategy used by English teachers at Al-Islam Boarding School as well as the perception of teachers and students on its effectiveness. The background of this research is the dominant use of Arabic in the school environment, which limits students' opportunities to practice speaking in English. The limitations of learning media such as projectors and language laboratories also require teachers' creativity in encouraging student participation. Although the teachers were not familiar with the theoretical term